Investigation of the effect of coagulation with high-energy methods of hemostasis implementation on the resected liver surface (experimental research). - Ternavskyi, O. P. (Medicni Perspektivi, 2018)
The peculiarity of using high-energy methods to implement hemostasis is in difficulty of comparing the degree of exposure to high temperature with the achievement of the desired effect, at the same time, excessive temperature in the area of impact leads to the formation of a layer of carbonized tissues or their evaporation. In order to analyze the peculiarities of changes in the liver parenchyma after coagulation with high-energy methods of hemostasis, an experiment that provided liver resection with coagulation of the resection surface using convection-infrared thermosurgical technology in a temperature mode of 600°C, bipolar electro-coagulation and high-frequency electric welding of living biological tissues was performed. The study analyzed the results of experimental studies on 25 outbred rabbits of different sex and age, weighing from 3350.0 g to 4180.0 g. Depending on the use of the high-energy coagulation method, 3 groups were formed: group 1 - high-frequency electric welding of living biological tissues; group 2 - bipolar electro-coagulation; group 3 - convection-infrared thermosurgical technology at a temperature mode of 600°C. The data of histological research were analysed. Statistical analysis was performed using SPSS Statistics. Studies have found that the average trend of the thickness of the disaggregation/disintegration zone is 1936 (1630.83-2523) μm in the 1st group, 648 (508.33-734.33) μm in the 2nd group and 470.6 (453.5-507) μm in the 3rd group. The zone of compacted parenchyma: the 1st group – 2732 (2591.5-2798.5) μm, the second group 4538 (4421.5-4687.5) μm (p=0.001). The results of the study indicate that the use of convection-infrared thermosurgical technology in a temperature mode of 600°C has a less destructive effect on the surrounding tissues as compared with bipolar electrocoagulation and high-frequency electric welding of biological tissues.